Cellulite: Presentation and management. (14th February 2022) - Arora, Gulhima; Patil, Anant; Hooshanginezhad, Zahra; Fritz, Klaus; Salavastru, Carmen; Kassir, Martin; Goldman, Mitchel P; Gold, Michael H.; Adatto, Maurice; Grabbe, Stephan; Goldust, Mohamad
Abstract: Background: Cellulite is a common dermatological condition with a female preponderance, affecting up to 90% post‐pubertal females. It is characterized with dimpling and denting of the skin surface, giving it a Peau d'orange appearance. Once considered to be a benign physiological isolated skin condition of only an esthetic concern, cellulite is now considered a pathological entity with systemic associations and a negative psychological impact on patients. Aims: The objective of this article was to discuss etiology, pathophysiology, and treatment of cellulite. Materials and methods: Literature was screened to retrieve articles from PubMed/Medline and Google Scholar and related websites. Cross‐references from the relevant articles were also considered for review. Review articles, clinical studies, systematic reviews, meta‐analysis, and relevant information from selected websites were included. Results: Several treatment options from lifestyle modifications and topical cosmetic therapies to energy‐based devices have been studied for its treatment. However, treatment remains a challenge despite many new modalities in the armamentarium. Laser and light therapies along with radiofrequency are useful treatment options with good safety profile. Acoustic wave therapy, subcision, and 1440‐nm Nd:YAG minimally invasive laser are beneficial in cellulite reduction. Discussion: Methodological differences in the trials conducted make it difficult to compare different treatment modalities. Conclusion: Overall, treatment needs to be individualized based on the patient characteristics and severity of the condition. A combination of treatments is often required in most patients for reducing cellulite.